Smart city and informatization : 7th International Conference, iSCI 2019, Guangzhou, China, November 12-15, 2019, Proceedings /: 7th International Conference, iSCI 2019, Guangzhou, China, November 12-15, 2019, Proceedings. (2019) - Unknown
No abstract available